11) x : 1,15 = 0,16;
х = 0,16 · 1,15
x = 0,184
12) 0,408 : x = 1,7;
x = 0,408 : 1,7
x = 0,24
13) (x + 9,14) : 7,2 = 5;
x + 9,14 = 7,2 · 5;
x = 36 - 9,14
x = 26,86
14) 2,2 - x: 0,3 = 0,13;
x : 0,3 = 2,2 - 0,13
x : 0,3 = 2,07
x = 2,07 · 0,3
x = 0,621
15) 5,6 : (x + 1,6) = 0,08
x + 1,6 = 5,6 : 0,08
x + 1,6 = 70
x = 70 - 1,6
x = 68,4
16) 5,6 : x + 0,16 = 0,3
5,6 : x = 0,3 - 0,16
5,6 : x = 0,14
x = 5,6 : 0,14
x = 40
17) 4,13 - 1,7x = 4,028
1,7x = 4,13 - 4,028
1,7x = 0,102
x = 0,102 : 1,7
x = 0,06
18) 64 : (2,4y + 19,04) = 3,2
2,4y + 19,04 = 64 : 3,2
2,4y + 19,04 = 20
2,4y = 20 - 19,04
2,4y = 0,96
y = 0,96 : 2,4
y = 0,4
1) 2 * ( x + 5 ) = 12 2) 84 : ( x - 3 ) = 42
х + 5 = 12 : 2 х - 3 = 84 : 42
х + 5 = 6 х - 3 = 2
х = 6 - 5 х = 2 + 3
х = 1 х = 5
проверка: проверка:
2 * ( 1 + 5 ) = 2 * 6 = 12 84 : ( 5 - 3 ) = 84 : 2 = 42
3) 3 * ( x + 4 ) = 33 4) 45 : ( x - 5 ) = 15
х + 4 = 33 : 3 х - 5 = 45 : 15
х + 4 = 11 х - 5 = 3
х = 11 - 4 х = 3 + 5
х = 7 х = 8
проверка: проверка:
3 * ( 7 + 4 ) = 3 * 11 = 33 45 : ( 8 - 5 ) = 45 : 3 = 15
5) 4 * ( x - 7 ) = 12 6) 6 * ( x - 2 ) = 24
х - 7 = 12 : 4 х - 2 = 24 : 6
х - 7 = 3 х - 2 = 4
х = 3 + 7 х = 4 + 2
х = 10 х = 6
проверка: проверка:
4 * ( 10 - 7 ) = 4 * 3 = 12 6 * ( 6 - 2 ) = 6 * 4 = 24
7) ( x + 3 ) * 3 = 27 8) ( x - 4 ) : 5 = 7
х + 3 = 27 : 3 х - 4 = 7 * 5
х + 3 = 9 х - 4 = 35
х = 9 - 3 х = 35 + 4
х = 6 х = 39
проверка: проверка:
( 6 + 3 ) * 3 = 9 * 3 = 27 ( 39 - 4 ) : 5 = 35 : 5 = 7
9) ( x - 3 ) : 2 = 12 10) ( x - 9 ) * 3 = 12
х - 3 = 12 * 2 х - 9 = 12 : 3
х - 3 = 24 х - 9 = 4
х = 24 + 3 х = 4 + 9
х = 27 х = 13
проверка: проверка:
( 27 - 3 ) : 2 = 24 : 2 = 12 ( 13 - 9 ) * 3 = 4 * 3 = 12
11) ( 3 x + 7 ) * 2 = 32 12) ( 2x - 20 ) : 32 = 6
3х + 7 = 32 : 2 2х - 20 = 6 * 32
3х + 7 = 16 2х - 20 = 192
3х = 16 - 7 2х = 192 + 20
3х = 9 2х = 212
х = 9 : 3 х = 212 : 2
х = 3 х = 106
проверка: проверка:
( 3 * 3 + 7 ) * 2 = 16 * 2 = 32 (2 * 106-20) :32 = 192:32 = 6
13) ( 42 + 2x ) : 2 = 32 14) ( 5x - 7 ) * 5 = 15
42 + 2х = 32 * 2 5х - 7 = 15 : 5
42 + 2х = 64 5х - 7 = 3
2х = 64 - 42 5х = 3 + 7
2х = 22 5х = 10
х = 22 : 2 х = 10 : 5
х = 11 х = 2
проверка: проверка:
( 42 + 2 * 11 ) : 2 = 64 : 2 = 32 ( 5 * 2 - 7 ) * 5 = 3 * 5 = 15
15) ( 13 - 2x ) * 3 = 27 16) ( 40 - 4x ) : 2 = 16
13 - 2х = 27 : 3 40 - 4х = 16 * 2
13 - 2х = 9 40 - 4х = 32
2х = 13 - 9 4х = 40 - 32
2х = 4 4х = 8
х = 4 : 2 х = 8 : 4
х = 2 х = 2
проверка: проверка:
( 13 - 2 * 2 ) * 3 = 9 * 3 = 27 ( 40 - 4 * 2 ) : 2 = 16
17) ( 63 - 9x ) : 3 = 15 18) 4 * ( x - 3 ) = 12
63 - 9х = 15 * 3 х - 3 = 12 : 4
63 - 9х = 45 х - 3 = 3
9х = 63 - 45 х = 3 + 3
9х = 18 х = 6
х = 18 : 9
х = 2
проверка: проверка:
( 63 - 9 * 2 ) : 3 = 45 : 3 = 15 4 * ( 6 - 3 ) = 4 * 3 = 12
19) 5 * ( x + 5 ) = 45 20) 3 * ( x - 7 ) = 9
х + 5 = 45 : 5 х - 7 = 9 : 3
х + 5 = 9 х - 7 = 3
х = 9 - 5 х = 3 + 7
х = 4 х = 10
проверка: проверка:
5 * ( 4 + 5 ) = 5 * 9 = 45 3 * ( 10 - 7 ) = 3 * 3 = 9
б)18:6=3
а)80:4=20
б)10:2=5 5-2=3 2*3=6